Attenuation of propranolol-induced bronchoconstriction by frusemide. Issue 10 (October 1997) - Myers, J D; Higham, M A; Shakur, B H; Wickremasinghe, M; Ind, P W
Abstract : BACKGROUND: Inhaled propranolol causes bronchoconstriction in asthmatic subjects by an indirect mechanism which remains unclear. Inhaled frusemide has been shown to attenuate a number of indirectly acting bronchoconstrictor challenges. The aim of this study was to investigate whether frusemide could protect against propranolol-induced bronchoconstriction in patients with stable mild asthma. METHODS: Twelve asthmatic subjects were studied on three separate days. At the first visit subjects inhaled increasing doubling concentrations of propranolol (0.25-32 mg/ml), breathing tidally from a jet nebuliser. The provocative concentration of propranolol causing a 20% reduction in FEV1 (PC20FEV1 propranolol) was determined from the log concentration-response curve for each subject. At the following visits nebulised frusemide (4 ml x 10 mg/ml) or placebo (isotonic saline) was administered in a randomised, double blind, crossover fashion. FEV1 was measured immediately before and five minutes after drug administration. Individual PC20FEV1 propranolol was then administered and FEV1 was recorded at five minute intervals for 15 minutes. Residual bronchoconstriction was reversed with nebulised salbutamol. RESULTS: Frusemide had no acute bronchodilator effect but significantly reduced the maximum fall in FEV1 due to propranolol: mean fall 18.2% after placebo and 11.8% after frusemide. The median difference in maximum % fall in FEV1 within individuals between study days was 3.6% (95% CI 1.2 to 11.7). CONCLUSIONS: Frusemide attenuates propranolol-induced bronchoconstriction, a property shared with sodium cromoglycate. Both drugs block other indirect challenges and the present study lends further support to the suggestion that frusemide and cromoglycate share a similar mechanism of action in the airways.